PENGARUH PENGGUNAAN MEDIA DIORAMA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS DI KELAS V SEKOLAH DASAR - Nurfirda Sari; Maruf; Syarifuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using diorama media on the learning outcomes of fifth-grade students of UPT SDN 169 Inpres Parambaddo. This study is a pre-experimental study with a one-group pretest–posttest design. The subjects of the study were all 28 fifth-grade students, with a total sampling technique. Data collection techniques were carried out through written tests, observations, and documentation. The instruments used were learning outcome tests and observation sheets. Data analysis techniques included descriptive statistical analysis and inferential statistics through normality tests, homogeneity tests, and paired sample t-tests. The results showed that the average pretest score of 49.71 was in the low category and had not achieved learning mastery, while the average posttest score increased to 84.86 with a high category and had achieved learning mastery. The results of the hypothesis test showed a significance value <0.05 so that H₀ was rejected and H₁ was accepted. Thus, it can be concluded that the use of diorama media has a significant effect on the science learning outcomes of class V students at UPT SDN 169 Inpres Parambaddo.